Dispositional optimism, sleep, and trait affective mediators: A latent variable approach - CHEN, Nicole Ruiying (Institutional Knowledge at Singapore Management University, 2024)
Dispositional optimism has been shown to be associated with better sleep. However, most existing studies rely on subjective assessments of sleep, which may not align with objective assessments of sleep. Additionally, research investigating the mechanisms underlying the association between optimism and sleep is lacking. Moreover, the confounding role of possible content overlap in measures relevant to the constructs of interest has been neglected. To address these gaps, we utilised latent variable analysis and investigated the mediating role of depression and trait anxiety across two large-scale studies (total N = 2312), with objective sleep measures included in Study 2. In Study 1 (N = 1010), a significant and medium association was found between optimism and better subjective sleep. Here, depression emerged as a robust mediator. In Study 2, both objective (N = 742) and subjective (N = 1302) sleep measures were analysed. Findings revealed a small and significant association between optimism and better subjective sleep, which was mediated by depression. However, optimism was not associated with objective sleep. Trait anxiety was a non-significant mediator in both studies. The current study suggests that the association between dispositional optimism and subjective sleep outcomes do not translate to similar results with objective sleep.